Sistem Pengelolaan Penjualan Dan Pemesanan Berbasis Web Di Bumdes Lestari Jaya - Heriyani Heriyani; Nova Lestari (LPPM Politeknik Jambi, 2020)
Village-Owned Enterprises (BUMDes) are village business institutions managed by the community and village government in an effort to strengthen the village economy which is formed based on the needs and potential of the village. The potential owned by BUMDes as a village community independent business institution in providing the welfare of the village community itself. The problem with BUMDes Lestari Jaya is that the sales system that still uses manual methods to sell these products will require a long time in the sales process, there is no interactive service for customers in ordering products other than coming directly to BUMDes or communication via telephone. In carrying out its business activities BUMDes Lestari Jaya does not allow selling manually. Therefore from the need for a website to facilitate the sale of products and ordering products. The results achieved in this study are a website based information system at BUMDes Lestarai Jaya using Xampp, PHP and MySQL. With this system, it is expected to be able to overcome existing problems and improve service quality for BUMDes Lestari Jaya customers. For BUMDes Lestari Jaya itself makes it easy for consumers to obtain information, to make online ordering ordering transactions and can help the BUMDes Lestari Jaya to increase and expand the range of product marketing.